The Elasticity of Factor Substitution Between Capital and Labor in the U.S. Economy: A Meta-Regression Analysis - Michael Knoblach; Martin Rößler; Patrick Zwerschke (Technische Universität Dresden, Center of Public and International Economics (CEPIE), 2016)
The elasticity of factor substitution between capital and labor is a crucial parameter in many economic fields. However, despite extensive research, there is no agreement on its value. Utilizing 738 estimates from 41 studies published between 1961 and 2016, this paper provides the first meta-regression analysis of capital-labor substitution elasticities for the U.S. economy. We show that heterogeneity in reported estimates is driven by the choice of estimation equations, the modeling of technological dynamics, and data characteristics. Based on the underlying meta-regression sample and a "best practice" specification, we estimate a long-run elasticity in the range of 0.6 to 0.7. For all estimated elasticities the hypothesis of a Cobb-Douglas production function is rejected.
urn:nbn:de:bsz:14-qucosa-210681
Keywords: E23; O30; O40; 330; Elasticity of Factor Substitution; Capital; Labor; Cobb-Douglas; CES Production Function; Meta-Regression Analysis; Meta Regression; Meta Analyse; Substitutionselastizität; Cobb-Douglas; CES Produktionsfunktion; Arbeit; Kapital